2011
DOI: 10.1038/jp.2011.167
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two-fingers technique and two-thumbs encircling hands technique of chest compression in neonates

Abstract: Objective: To compare the proportion of correct placements (POCP) between 'two-fingers' and 'two-thumbs' techniques of chest compression among neonates of various gestations.Study Design: Two-fingers and two-thumbs spans of 32 adult rescuers were individually compared with the inter-nipple line to sterno-xiphoid junction distance of 39 neonates. 'Correct placement' was defined if two-fingers/two-thumbs span was equal to or less than the inter-nipple line to sterno-xiphoid junction distance. The POCPs was compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…An assumption was made that the lower third of the sternum was the best position for compressions. 204 Term and preterm babies: Correct positioning on the chest was determined to be much better with the 2-thumb method in both groups of babies, although incorrect placements were found for both techniques in infants less than 1500 g. Chest x-ray analysis of term and preterm babies 205 found the heart to be under the lower third of the sternum. Chest CT scans of infants (mean age, 4.7 months), compared with adult thumb measurements on a manikin, comparing the 2-thumb method side by side or superimposed, 206 demonstrated that the side-by-side method increases the likelihood of other organs (lungs and liver) being under the points of compressions application.…”
Section: Best Location On the Sternummentioning
confidence: 99%
“…An assumption was made that the lower third of the sternum was the best position for compressions. 204 Term and preterm babies: Correct positioning on the chest was determined to be much better with the 2-thumb method in both groups of babies, although incorrect placements were found for both techniques in infants less than 1500 g. Chest x-ray analysis of term and preterm babies 205 found the heart to be under the lower third of the sternum. Chest CT scans of infants (mean age, 4.7 months), compared with adult thumb measurements on a manikin, comparing the 2-thumb method side by side or superimposed, 206 demonstrated that the side-by-side method increases the likelihood of other organs (lungs and liver) being under the points of compressions application.…”
Section: Best Location On the Sternummentioning
confidence: 99%
“…Because ventilation is the most effective action in neonatal resuscitation and because chest compressions are likely to compete with effective ventilation, rescuers should ensure that assisted ventilation is being delivered optimally before starting chest compressions. 3 Compressions are delivered on the lower third of the sternum [153][154][155][156] to a depth of approximately one third of the anteriorposterior diameter of the chest (Class IIb, LOE C-LD). 157 Two techniques have been described: compression with 2 thumbs with the fingers encircling the chest and supporting the back (the 2-thumb technique) or compression with 2 fingers with a second hand supporting the back (the 2-finger technique).…”
Section: Chest Compressions Nrp 605 Nrp 895 Nrp 738 Nrp 862mentioning
confidence: 99%
“…Compressions are delivered on the lower third of the sternum [153][154][155][156] to a depth of approximately one third of the anterior-posterior diameter of the chest (Class IIb, LOE C-LD). 157 Two techniques have been described: compression with 2 thumbs with the fingers encircling the chest and supporting the back (the 2-thumb technique) or compression with 2 fingers with a second hand supporting the back (the 2-finger technique).…”
mentioning
confidence: 99%